2001
DOI: 10.1111/1467-9450.00242
|View full text |Cite
|
Sign up to set email alerts
|

The Tromsø Social Intelligence Scale, a self‐report measure of social intelligence

Abstract: Social intelligence is a construct that not only appeals to laymen as a relevant individual difference but also has shown promising practical applications. Nevertheless, the use of social intelligence in research and applied settings has been limited by definitional problems, difficulties in empirically differentiating social intelligence from related constructs, and the complexity of most existing measures of social intelligence. The goal of the present research was to address some of these obstacles by desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
313
2
38

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 313 publications
(362 citation statements)
references
References 22 publications
9
313
2
38
Order By: Relevance
“…Norwegian researchers D.H. Silvera, M. Martinussen and T. Dahl (Silvera et al, 2001) developed a test for measuring social intelligence -the Tromsø Social Intelligence Scale which was also used in the present study. The authors identified three SI components: (a) social information processing, (b) social skills and (c) social awareness.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Norwegian researchers D.H. Silvera, M. Martinussen and T. Dahl (Silvera et al, 2001) developed a test for measuring social intelligence -the Tromsø Social Intelligence Scale which was also used in the present study. The authors identified three SI components: (a) social information processing, (b) social skills and (c) social awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Social information processing describes cognitive processes involved in social interaction: the awareness and acceptance of social situations; the ability to listen to others and fully understand implied SHS Web of Conferences or partially expressed thoughts and feelings; the defining and setting of targets, the search for feedback or social solutions (Silvera et al, 2001;Lopes et al, 2004;Meijs et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations